2012
DOI: 10.1090/s0002-9947-2012-05739-4
|View full text |Cite
|
Sign up to set email alerts
|

Closed orbits and uniform $S$-instability in geometric invariant theory

Abstract: In this paper we consider various problems involving the action of a reductive group G on an affine variety V . We prove some general rationality results about the G-orbits in V . In addition, we extend fundamental results of Kempf and Hesselink regarding optimal destabilizing parabolic subgroups of G for such general G-actions.We apply our general rationality results to answer a question of Serre concerning the behaviour of his notion of G-complete reducibility under separable field extensions. Applications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 36 publications
(58 reference statements)
0
66
0
Order By: Relevance
“…This result motivates the following definition introduced by Levy (see [15] and also [3,Definition 3.8]). …”
Section: Ps Polystabilitymentioning
confidence: 72%
“…This result motivates the following definition introduced by Levy (see [15] and also [3,Definition 3.8]). …”
Section: Ps Polystabilitymentioning
confidence: 72%
“…The following theorem answers a question of Serre: [4,Ex. 5.12], we showed that Theorem 1.1 holds when G = GL(V ).…”
Section: Introductionmentioning
confidence: 94%
“…Tits [4] utilizes methods from geometric invariant theory and the concept of optimal destabilizing parabolic subgroups.…”
Section: The Centre Conjecture For Spherical Buildingsmentioning
confidence: 99%
See 2 more Smart Citations